Inflammatory Pseudotumor of the Temporal Bone: Three Cases and a Review of the Literature - Huiqin Tian; Tingting Liu; Cong Wang; Lijun Tang; Zhibin Chen; Guangqian Xing (Case Reports in Medicine)
Inflammatory pseudotumor (IP) is a clinically aggressive but histologically benign condition of unknown cause. Its appearance in the temporal bone is uncommon. We present clinical, radiological, and histopathologic findings of three cases originating in the temporal bone. In the first case, a simultaneous IP of the temporal bone and parotid gland was found with histopathologic confirmation. In the second case, an enlarged cervical node, which was also believed to be related to IP, was observed accompanied with the temporal lesion. While the third case presented with chronic suppurative otitis media. Two of them were treated by surgery alone with complete resolve of the diseases. Another one underwent tympanomastoidectomy in combination with oral steroids, radiation, and chemotherapy, but the IP still recurred. A comprehensive review of the literature on clinical features of the temporal pseudotumor was conducted.